Transport of Human Reproductive Samples and Regulatory Security Controls Systems in EU Airports - Monaco, Mario (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The singularity of transporting human reproductive biological material contin-ues to grow due to the effectiveness of cryo-preservation techniques that al-low transportation of gametes and embryos through different means. While other places lack specific protocols on the matter, security controls at the air-ports are quite systematized. The analysis of regulation on this sector repre-sents an unavoidable need in view of being able to guarantee the quality and clinical security of these shipments and circulation in a safe environment. In this area, the guidelines are set by international regulatory provisions which constitutes the reference on the matter and whose implementation has not pro-duced uniform results. The subject is in continuous evolution and interpreta-tion also depending on the development of science and technology.
Keywords: Embryo; gametes; transport; airport regulation; security control